The synthetic opioid fentanyl increases HIV replication in macrophages - Janani Madhuravasal Krishnan; Ling Kong; Heidi L. Meeds; Krishna M. Roskin; Mario Medvedovic; Kenneth E. Sherman; Jason T. Blackard (PLoS ONE, 2025)
Background The illicit use of synthetic opioids such as fentanyl has led to a serious public health crisis in the US. People with opioid use disorder are more likely to contract infections such as HIV and viral hepatitis and experience more severe disease. While several drugs of abuse are known to enhance viral replication and suppress immunologic responses, the effects of synthetic opioids on HIV pathogenesis have not been investigated thoroughly. Thus, we examined the impact of fentanyl on HIV replication and chemokine receptor expression in the U937 cell line and monocyte-derived macrophages (MDMs). Methods U937 cells were exposed to varying concentrations of fentanyl. Expression levels of the CXCR4 and CCR5 chemokine receptors were measured in cell lysates. HIV p24 antigen was quantified in culture supernatants by ELISA, and HIV proviral DNA was quantified in cells using SYBR real-time PCR targeting the pol gene. RNAseq was performed to characterize cellular gene regulation in the presence of fentanyl. Results Fentanyl induced HIV p24 expression and proviral DNA levels in U937 cells and in primary MDMs. The opioid antagonist naltrexone blocked the effect of fentanyl and reversed the expression of HIV protein and proviral DNA. Fentanyl led to a non-significant decrease in CXCR4 and CCR5 protein levels in U937 cells. RNA sequencing identified several differentially expressed genes in cells infected with HIV and exposed to fentanyl compared to infected cells with no drug exposure. Several microRNAs were also differentially expressed upon fentanyl exposure but not at a statistically significant level. Conclusion These data demonstrate that the synthetic opioid fentanyl can promote HIV replication in macrophages. As higher HIV levels lead to accelerated disease progression and a higher risk of transmission to others, further research is needed to better understand opioid-virus interactions and to develop new and/or optimized treatment strategies for people living with HIV and opioid use.